Розроблення електронних освітніх ресурсів у системі кроскультурної підготовки майбутніх фахівців галузі туризму - Сідоров, Вадим (My University, 2017)
У статті автор пропонує методику розроблення електронних освітніх ресурсів у системі кроскультурної підготовки майбутніх фахівців галузі туризму – методику корпоративного веб-вузла у процесі створення електронного посібника «Культурознавство: перехрестя культур». Визначено, що застосування методики корпоративного веб-вузла для розроблення електронних освітніх ресурсів здійснюється у чотири етапи: «Початок», «Майстер», «Контент», «Запуск». In the article the author proposes a methodology for the development of electronic educational resources in the system of cross-cultural training of future specialists in the field of tourism - the methodology of the corporate web site in the process of creating an electronic manual "Cultural Studies: cross-cultural". It is determined that the application of the methodology of the corporate web site for the development of electronic educational resources is carried out in four stages: "Beginning", "Master", "Content", "Launching". The joint work of students, Ukrainians and foreigners on the project "Creating an electronic manual" Cultural Studies: cross-cultural "contributed to the socio-cultural adaptation of foreign students: overcoming the language barrier; entry into the student's environment; mastering the basic norms of the cross-cultural team; developing a style of behavior; formation of a stable positive attitude towards the future profession of a specialist in the field of tourism. Students have improved the skills of searching and analyzing information, working in various information systems, receiving cross-cultural knowledge, developing communication skills and cross-cultural communication, and overcoming the main barriers in communication (cross-cultural competence). Students have improved the skills of searching and analyzing information, creating computer presentations, developing websites using the Microsoft FrontPage information system, and using Internet services (information and communication competence).
Keywords: електронний освітній ресурс; кроскультурна підготовка; компетентність; інформаційно-комунікаційна компетентність; туризм